Nghiên cứu biến tính bề mặt ống cacbon nano bằng phản ứng este hóa Fischer - Kháng, Đỗ Quang; Vân, Chu Anh; Hải, Lê Hồng; Oanh, Hồ Thị (Vietnam Journal of Chemistry, 2015)
In this work, carbonnanotubes (CNT) was firstly purified to remove residual metal catalyst in the preparation process. Afterward, H2O2/NH3 mixture was used as the oxidizing agent for CNT treatment in order to form functional groups COOH and NH2 on CNT surface. Polyethyleneglycol and bis(3-triethoxysilylpropyl) tetrasulfide (TESPT) were then grafted onto the oxidized surface of CNT under appropriate conditions of Fischer esterification reaction. The structure of CNT and modified CNT were characterized by infrared spectroscopy, Raman, transmission electron microscopy (TEM) and weight thermal analysis (TGA). The results have proven that organic functional groups (-COOH and -NH2) were successfully attached onto the surface of CNT and the content of the organic functional group is about 27.85 %. By the CNT modified with PEG and TESPT the content of –CO-PEG and –CO-TESPT are about 24.66 % and 3.28 %, respectively.